(untitled) (CIPEEX, 2025)
Abstract: Chronic Obstructive Pulmonary Disease (COPD), the third leading cause of death globally, poses a significant public health challenge in Goiás, characterized by a high mortality rate and a scarcity of ICU beds. This study aimed to investigate the correlation between COPD mortality and ICU bed availability in Goiás, emphasizing the pivotal role of nursing in patient care. A retrospective, cross-sectional quantitative study was conducted using data from DATASUS and Goiás Health Indicators (2019-2022). The results revealed that Goiás recorded 6,672 COPD-related deaths during this period, despite only 24 of the 246 municipalities having access to ICU beds. These findings underscore the critical importance of nursing strategies in managing COPD patients. Early identification and prevention of COPD decompensation through meticulous nursing assessments are essential. Moreover, nurses’ expertise in inhalation techniques, such as oxygen therapy (low flow, high flow, non-invasive ventilation, hyperbaric oxygen therapy), is crucial for optimizing patient outcomes. These interventions not only improve patients’ conditions but also reduce stress and hospitalizations. Depending on the patient’s clinical status, available infrastructure, and adequate professional support, these techniques can be administered outside of ICUs, offering a viable alternative to address the shortage of ICU beds in Goiás.